ANALISIS PROSES RESTATEMENT DALAM RANGKA PENERAPAN PP NOMOR 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL PADA LAPORAN KEUANGAN KONSOLIDASI KABUPATEN SEKADAU TAHUN 2014. - B41112029, Siska Andriyani B41112029 siska (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
SISKA ANDRIYANI B41112029 Changes in financial governance of the Republic of Indonesia has always been done to increase financial accountability and transparency of the government. This is evidenced by the issuance of Government Regulation 71 of 2010 on the application of accrual-based government accounting standards.  The implementation of this regulation must be made by each government at the latest by 2015. The first step that must be taken is to restate their financial statement (Balance Sheet) in 2014. Data analysis methods used in this study is a qualitative method. From analyzing data and after restatement process has been done, there is a significant changes of the financial condition of Sekadau Regency, that is stated at the decline in the number of assets listed on the balance sheet. This is because there are a few adjustments to the balance sheet accounts in accordance with full accrual basis ruled in Government Regulation No. 71 of 2010. In addition, also found that the Sekadau Regency do not have data on the results of the investments made over the last few years yet, thus affecting the restatement process of financial statement.  Of the existing conclusions , the researchers advise that the data related to the results of these investments could completed soon, so that the process of restatement made ??to its financial statements  can be fully implemented. In addition, sustainability upgrades to human resources of Sekadau Regency also must be done  to produce financial statements that relevant and transparent based on Government Regulation  71 of 2010.  Keywords: Government Accounting, Restatement, Accrual